An in vitro micro-CT assessment of bioactive restorative materials interfacial adaptation to dentin - Priyanka Angadala; Jyothi Mandava; Ravichandra Ravi; Koteswar Rao Hanumanthu; Prasanthi Penmatsa; Hema Pulidindi (Dental Research Journal, 2022)
Background: The background of this study was to improve the longevity of a restoration and optimal adaptation of restorative material to the prepared cavity walls is crucial. The study aimed to evaluate the interfacial adaptation of Activa, Micron, and Predicta bulk bioactive restorative materials to coronal dentin using micro-computed tomography (CT) analysis. Materials and Methods: In this in vitro micro-CT assessment study, Class II mesio- and disto-occlusal cavities were prepared on 60 extracted human mandibular molar teeth. After etching and bonding procedures, all the mesial cavities (n = 60) were restored with Tetric N-Ceram and the disto-occlusal cavities with Activa or Micron or Predicta bioactive (n = 20 each) restoratives. Interfacial gap percentages were evaluated under micro-CT before (baseline) and after thermo-mechanical load cycling (TMC). Acquired data were analyzed statistically using one-way analysis of variance, Paired t-test, and Tukey's multiple post hoc procedures, at P < 0.05 level of significance. Results: The interfacial gap percentages were lowest for Predicta bioactive and highest for the Micron group (P < 0.05). The number of gaps increased significantly after TMC in all the groups (P < 0.05). The adaptation of tested materials was inferior to axial wall and pulpal floor, whereas considerably better adaptation was observed on buccal and lingual walls. Conclusion: Predicta bioactive followed by Activa bioactive has shown superior interfacial adaptation, whereas Micron bioactive demonstrated maximum microgaps compared to nanohybrid composite. Artificial aging with TMC has a negative influence on the internal adaptation of all tested materials.